ПЕРСПЕКТИВЫ ДИВЕРСИФИКАЦИИ МИНЕРАЛЬНО-СЫРЬЕВОГО КОМПЛЕКСА МАГАДАНСКОЙ ОБЛАСТИ: ЦВЕТНЫЕ МЕТАЛЛЫ - Гальцева Н.В.; Шарыпова О.А. (My University, 2006)
The mineral resource complex (MRC) plays a key role in the economy of the Magadan Oblast. The basis of the complex is formed by gold and silver mining and to a lesser extent coal production. At the same time, the Magadan Oblast has a significant potential to diversify its MRC. In addition to gold, silver, and coal, other types of minerals that may be mined there are non-ferrous and platinum metals, crude oil and natural gas, peat, zeolite, limestone, gypsum, fluorite, and barite Among the promising lines of MRC diversification are development of the resource base and getting access to the world non-ferrous metals market. Investigations run in the Magadan Oblast determined the following six non-ferrous metal occurrences commercial development of which is practicable at the current level of prices and costs: The Oroyokskaya copper prospect and Oroyok copper ore occurrence; The Bokhapchinskoye tungsten deposit and Malinovaya tungsten ore zone; The Aksu molybdenum ore occurrence and Oldyaninsky ore cluster (the Vecherneye and Khrustalnoye ore occurrences). Development of the each of the above prospects will enable increasing receipts of the Magadan oblast consolidated budget from 0.8% to 26.6%, and the share of the government subsidy to the territory budget that came to 51.5% in 2005 will thereby decrease. Total earnings will surpass the 2005 subsidy (4,639.5 million rubles) by a factor of 1.12.